Rancang Bangun dan Pengujian Alat Pengering Biji Kopi Tenaga Listrik Dengan Pemanfaatan Energi Surya - Oktaviani, Sis; Suhardiman, Suhardiman (Politeknik Negeri Bengkalis, 2023)
Currentely several agritultural processing houses in simpang tonang still tend to house traditional methods in their aplication.Product drying is a form of post harvest handling that has been highlighted by agricultural observes.The process of drying agricultural product in general still uses natural drying, namely by drying in this way,of course,,really depends on weather condition and can only be done in the morning until noon.This of course disrupts the drying process of the product noon.This of coorse disrupts the drying process of the product and takes a long time.Therefore,a dryer is needed which can be an alternative tool when natural drying cannot be done.In this study ,a coffe bean dryer was built with the help of electrical energi is the result of convering solar energy with the help of photovoltaicwhich is stored first in the battery.And the calculations show that a 12Vbattery with a current of 70Ampere has a power of 840watts.The battery provides approximately 40watts 120hours.Meanwhile, the power used by the tool is 295watt hours.This tool can dry all types of coffe beans.